2005
DOI: 10.1111/j.0022-1112.2005.00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability in diet and foraging behaviour between sexes and ploidy forms of the hybridogeneticSqualius alburnoidescomplex (Cyprinidae) in the Guadiana River basin, Portugal

Abstract: Samples of the Squalius alburnoides complex, a hybridogenetic Iberian minnow composed of diploid, triploid and, less commonly, tetraploid forms, were collected from a tributary of the Ardila River (Guadiana River basin) between February 1999 and January 2001. Seasonal variation in diet was evident, and was probably linked to prey availability. Distinct foraging behaviours between ploidy forms were found towards several prey items, suggesting that diploid adult males fed mostly near the surface, whereas diploid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Investigations on some other diploid-polyploid complexes in vertebrates revealed that hybrid biotypes can show different grades of similarity when compared with diploid parental forms; a variability pattern that corresponds with the gene-dose effect was noticed in the Cobitis complex from the Moscow R. (Vasil'ev et al 1989), Poeciliopsis monacha -P. lucida (Schultz 1969, Cimino 1972 and Phoxinus eos -P. neogaeus fish complexes (Goddard and Schultz 1993). In the Iberian "alburnoides" complex of cyprinids the triploid biotype is completely indistinguishable from the sympatric parental species, in spite of the ecological differences between them (Martins et al 1998, Gomes-Ferreira 2005. Diploid and triploid hybrids of Cobitis sinensis -Iksookimia longicorpus complex display an intermediate character between both parents in body proportions and coloration, and no differences between the two biotypes are mentioned (Kim and Lee 1990, 1995.…”
Section: Discussionmentioning
confidence: 98%
“…Investigations on some other diploid-polyploid complexes in vertebrates revealed that hybrid biotypes can show different grades of similarity when compared with diploid parental forms; a variability pattern that corresponds with the gene-dose effect was noticed in the Cobitis complex from the Moscow R. (Vasil'ev et al 1989), Poeciliopsis monacha -P. lucida (Schultz 1969, Cimino 1972 and Phoxinus eos -P. neogaeus fish complexes (Goddard and Schultz 1993). In the Iberian "alburnoides" complex of cyprinids the triploid biotype is completely indistinguishable from the sympatric parental species, in spite of the ecological differences between them (Martins et al 1998, Gomes-Ferreira 2005. Diploid and triploid hybrids of Cobitis sinensis -Iksookimia longicorpus complex display an intermediate character between both parents in body proportions and coloration, and no differences between the two biotypes are mentioned (Kim and Lee 1990, 1995.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, the habitat change during the spring months undermines the spawning activity and consequently the sustainability of future population stocks (Lobón-Cerviá and Fernandez-Delgado, 1984). The habitat increase in calandino during this period can be ecologically tricky due to the habitat plasticity of this species (Doadrio, 2011;Gomes-Ferreira et al, 2005), as well as its characteristic adoption for an rselection strategy as an evolutionary response to frequently disturbed environments (Bernardo et al, 2003). Above all, one should not ignore the fact that the relationships between fish assemblages and habitat are extremely complex (e.g., Diana et al, 2006;Hubert and Rahel, 1989;Santos et al, 2011), a consequence of the actual natural conditions (Poff and Allan, 1995;Poff et al, 1997) that when disrupted may allow the expansion of more generalist and opportunistic fauna (Poff and Ward, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Fish populations were sampled during 2012 and 2013 at undisturbed or minimally disturbed sites in the Ocreza basin, an essential requisite when studying habitat preferences of stream fishes in order to reflect their optimal habitat (Gorman and Karr, 1978). Sampling occurred in autumn (November 2012), spring (May 2013) and early summer (June 2013) when there is full connectivity among instream habitats.…”
Section: Fish Datamentioning
confidence: 99%
“…The results of the present study are useful not only to improve an understanding of the species' seasonal and size-related habitat requirements but also to inform river restoration practices elsewhere, Submerged aquatic macrophytes are a source of complex and important cover for fish, especially younger stages, because they provide not only hiding places but also feeding habitats through harbouring the invertebrates on which these species feed (Dukowska, Kruk, & Grzybkowska, 2014;Gomes-Ferreira, Ribeiro, Costa, Cowx, & Collares-Pereira, 2005). In addition, increasing the number of sheltered pools, which are important habitats for barbel and calandino, should also be considered.…”
Section: Implications For River Restoration and Managementmentioning
confidence: 98%